Preschoolers' prosocial behavior in groups—Testing effects of dominance, popularity, and friendship - Anne Katerkamp; Lisa Horn (Frontiers in Psychology)
Prosocial, other-benefitting behavior is a fundamental aspect of human social behavior. In the microsystem of their natural social groups, preschool children have to decide not only whether, but also whom to share with and help on a daily basis. In a study with 108 preschool children from five different childcare facilities in Vienna, we examined how individual measures of dominance and popularity of both the actor and the recipient, as well as their friendship influenced their prosocial behavior in a group setting. We assessed popularity and friendship with age-appropriate sociometric interviews and tested two types of dominant behavior (i.e., contest and scramble) as well as two types of prosocial behavior (i.e., sharing and helping) in groups of familiar peers. Participants were tested in their regular socio-ecological niches, thereby preserving and taking into account social dynamics that influence—and are influenced by—interactions within the group. We found that both types of prosocial behavior were directed more often toward friends than toward children that were not considered as friends. Likelihood to share was increased by both the actor's and the recipient's dominance in the contest game. Furthermore, we found that helping was preferentially performed by as well as directed toward older children and that dominant children more frequently received help. Group size and testing sequence had some additional effects on sharing and helping. Our findings suggest that sharing and helping have similar as well as different antecedents and underlying motivations and depend on social relationships between the children. Such effects can be examined more effectively when taking a developmental-ecological approach and investigating prosocial behavior in children's natural social environment.